Larvae of Abachrysa eureka (Banks) (Neuroptera: Chrysopidae: Belonopterygini): descriptions and a discussion of the evolution of myrmecophily in Chrysopidae - Tauber, Catherine A.; Kilpatrick, Shelby Kerrin; Oswald, John D. (Zootaxa, 2020)
Here we describe the first and third instars and the egg of the New World chrysopid Abachrysa eureka (Banks). Like other members of the tribe Belonopterygini, this species is myrmecophilic. Comparisons of Abachrysa larval and egg characteristics with those reported from four other belonopterygine genera indicate that Abachrysa more closely resembles the Old World Calochrysa and Italochrysa than the New World Vieira and Nacarina. The three genera Abachrysa, Calochrysa and Italochrysa all have large eggs, accelerated embryonic development, and an elaborate set of morphological modifications for larval debris carrying, an important defense against ant attack. This pattern of shared features is consistent with the phylogenies recovered in recent molecular studies that place the New World genera Vieira and Nacarina basal to Abachrysa and the Old World genera. Our assessment of current morphological information in relation to the molecular studies indicates the following sequence: (i) The form of belonopterygine myrmecophily that is currently expressed in the basal lineages (Nacarina and perhaps Vieira) originated in the New World and does not involve elaborate larval modifications for debris carrying. (ii) Myrmecophily that is based on a correlated set of developmental and morphological traits subserving debris carrying evolved in the New World when Abachrysa diverged. (iii) Subsequently, the debris-carrying clade of Belonopterygini underwent a significant radiation in the Old World, but not in the New World.